Scaling potential of beam-splitter-based coherent beam combination - Mueller, Michael; Aleshire, Christopher; Buldt, Joachim; Stark, Henning; Grebing, Christian; Klenke, Arno; Limpert, Jens (Optics Express, 2021)
The impact of nonlinear refraction and residual absorption on the achievable peak- and average power in beam-splitter-based coherent beam combination is analyzed theoretically. While the peak power remains limited only by the aperture size, a fundamental average power limit is given by the thermo-optical and thermo-mechanical properties of the beam splitter material and its coatings. Based on our analysis, 100 kW average power can be obtained with state-of-the-art optics at maintained high beam quality (M2 ≤ 1.1) and at only 2% loss of combining efficiency. This result indicates that the power-scaling potential of today’s beam-splitter-based coherent beam combination is far from being depleted. A potential scaling route to megawatt-level average power is discussed for optimized beam splitter geometry.
CRIS-Team Scopus Importer:2023-04-20